The Natural Stone Waste: Regional Policies and Their Implementation - Faudzi, Azwar; Umam, Khoirul; Lita, Lita; Khumayah, Siti; Lestari, Aghnia Dian (ann4publisher@gmail.com, 2025)
Background. Various cases of environmental pollution, such as the disposal of natural stone found in Cirebon Regency, particularly in Dukupuntang District, result in waste from the cutting process. Business operators utilize flowing water to cool the natural stone cutting machines. Unfortunately, the waste generated is directly discharged into rivers without undergoing treatment, leading to pollution in the river flow. Aims. The objective is to understand the implementation of policies, strategies, and the factors that support and hinder them, as well as the steps taken by the government. By utilizing George C. Edward III's theory, the researcher will examine policy implementation, covering aspects of communication, resources, disposition, and bureaucratic structure. Methods. The research method used is a descriptive qualitative approach, where the natural stone industry players and the surrounding community will be the subjects of observation. Result. The results of this study indicate that the implementation of environmental policies in Cirebon Regency has not yet reached an optimal level. However, several hindering factors need to be addressed, one of which is the Wastewater Treatment Plant (WWTP), which requires further processing. Conclusion. Efforts that need to be undertaken by the Department in managing natural stone waste include communicating through the media, using communication or educational methods, and conducting supervision and guidance. Implementation. Reporting on efforts already undertaken, allocating budget funds, and fostering public awareness, all of which are crucial for effectively implementing policies related to natural stone waste